2008
DOI: 10.1111/j.1600-6143.2008.02298.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Aspiration of Gastric Fluid Induces the Development of Obliterative Bronchiolitis in Rat Lung Transplants

Abstract: Long-term survival of a pulmonary allograft is currently hampered by obliterative bronchiolitis (OB), a form of chronic rejection that is unique to lung transplantation. While tracheobronchial aspiration from gastroesophageal reflux disease (GERD) has clinically been associated with OB, no experimental model exists to investigate this problem. Using a WKY-to-F344 rat orthotopic left lung transplant model, the effects of chronic aspiration on pulmonary allograft were evaluated. Recipients received cyclosporine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 29 publications
2
38
0
1
Order By: Relevance
“…An intriguing model of lung transplantation in ferrets also develops OB-like lesions (112). Finally, the role of innate immune activation in augmenting OB has also been evaluated using the rat lung transplant model with intratracheal gastric fluid challenge (113).…”
Section: Cladmentioning
confidence: 99%
“…An intriguing model of lung transplantation in ferrets also develops OB-like lesions (112). Finally, the role of innate immune activation in augmenting OB has also been evaluated using the rat lung transplant model with intratracheal gastric fluid challenge (113).…”
Section: Cladmentioning
confidence: 99%
“…Further, we have shown that chronic aspiration can exacerbate asthmalike hypersensitivity in mice (Barbas et al 2008). The wide range of pulmonary pathology that can be influenced by chronic aspiration is further demonstrated by the observations that chronic aspiration can induce either accelerated acute rejection (Hartwig et al 2006) or the development of obliterative bronchiolitis (Li et al 2008) in rat lung transplant models. The studies described in this manuscript are intended to provide the first in vitro investigations aimed at elucidating the mechanisms associated with chronic aspiration in the pathogenesis of pulmonary disease.…”
Section: Introductionmentioning
confidence: 77%
“…These lesions may play an important role in exacerbation of FEV 1 subsequent to COPD exacerbations, unlike true constrictive BO that is fused to the bronchiolar wall and obliterates the lumen. In a recent experimental study, Li et al [29] reported histological evidence consistent with BO development in lung allografts after inducing chronic gastric fluid aspiration in a rat model that utilized immunosuppression to avoid acute rejection. However, the BO-like lesions observed in the present reflux animal lungs did not result from lung transplants or cyclosporine treatments.…”
Section: Discussionmentioning
confidence: 99%